Recognition of Hg 2+ and Cr 3+ in physiological conditions by a rhodamine derivative and its application as a reagent for cell-imaging studies - Saha, Sukdeb; Mahato, Prasenjit; Reddy, Upendar G.; Suresh, E.; Chakrabarty, Arindam; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Inorganic Chemistry, 2012)
A new rhodamine-based receptor, derivatized with an additional fluorophore (quinoline), was synthesized for selective recognition of Hg2+ and Cr3+ in an acetonitrile/HEPES buffer medium of pH 7.3. This reagent could be used as a dual probe and allowed detection of these two ions by monitoring changes in absorption and the fluorescence spectral pattern. In both instances, the extent of the changes was significant enough to allow visual detection. More importantly, the receptor molecule could be used as an imaging reagent for detection of Hg2+ and Cr3+ uptake in live human cancer cells (MCF7) using laser confocal microscopic studies. Unlike Hg(ClO4)2 or Hg(NO3)2 salts, HgCl2 or HgI2 failed to induce any visually detectable change in color or fluorescence upon interaction with L1 under identical experimental conditions. Presumably, the higher covalent nature of HgII in HgCl2 or HgI2 accounts for its lower acidity and its inability to open up the spirolactam ring of the reagent L1. The issue has been addressed on the basis of the single-crystal X-ray structures of L1·HgX2 (X– = Cl– or I–) and results from other spectral studies.

Recognition of Hg2+ion through restricted imine isomerization: crystallographic evidence and imaging in live cells - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Suresh, E.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic Letters, 2012)
A newly synthesized imine-based receptor (L) showed remarkable specificity toward the Hg2+ ion in aqueous media over other metal ions. Coordination of L to Hg2+ induces a turn-on fluorescence response. This was explained based on the restricted imine isomerization along with PET on coordination to Hg2+. X-ray structural evidence tends to favor a C–C bond rotation rather than C═N isomerization for adopting a favorable conformation in L for coordination to Hg2+. This reagent could be used for imaging the accumulation of Hg2+ ions in HeLa cells.